A Case of an Acquired Factor VIII Inhibitor Complicated by Multiple Treatment-Related Opportunistic Infections and Review of the Literature - Anna L. Hutchinson; Yi Ling Tan; Giselle Kidson-Gerber (Case Reports in Hematology)
This case report describes a patient with an idiopathic acquired Factor VIII inhibitor and severe bleeding. She was treated with rituximab after failing first-line treatment with steroids and cyclophosphamide. Two months following rituximab treatment, our patient developed a succession of severe opportunistic infections requiring intensive care unit admission. Over a period of 12 weeks she required treatment for Pseudomonas aeruginosa septicaemia, herpes simplex gingivostomatitis and pharyngotonsillitis, clostridium difficile-related diarrhoea, systemic cytomegalovirus infection, pneumocystis jiroveci, and invasive pulmonary aspergillosis lung infections. After significant rehabilitation, the patient was finally discharged following a 5-month admission. This case highlights the complexity of balancing a life-threatening condition with the side effects of treatment. It also raises the issue of routine prophylaxis for immunosuppression in nonmalignant conditions, which will become a common dilemma with the expanding indications for rituximab use.